2010
DOI: 10.1002/ejoc.200901328
|View full text |Cite
|
Sign up to set email alerts
|

A Metal–Macrocycle Complex as a Fluorescent Sensor for Biological Phosphate Ions in Aqueous Solution

Abstract: We synthesized tetraazamacrocycles 1 and 2 bearing two anthryl groups as sidearms, both of which exhibited high selectivity for the Zn II ion in switching-on-type responses in aqueous solution. For ligand 1, Zn II is coordinated by four nitrogen atoms of the macrocycle and two amino groups on the pendent arms, which results in proximity between the two fluorophores. So, 1-Zn II shows obvious excimer emission in aqueous solution. When PPi or ATP was added (pH 7.4), the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 58 publications
0
21
1
Order By: Relevance
“…Upon addition of Cu 2+ ions, the emission peaks of anthracene fluorophore (at around 400 nm, 420 nm and 440 nm) decreased gradually. Different from our reported work, there was no significant increase of the excimer emission at 520 nm, which suggested that metal ions binding process did not make anthryl groups in close proximity . Compared to other metal ions, Cu 2+ induced fluorescence reduction was the most significant (Figure b).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…Upon addition of Cu 2+ ions, the emission peaks of anthracene fluorophore (at around 400 nm, 420 nm and 440 nm) decreased gradually. Different from our reported work, there was no significant increase of the excimer emission at 520 nm, which suggested that metal ions binding process did not make anthryl groups in close proximity . Compared to other metal ions, Cu 2+ induced fluorescence reduction was the most significant (Figure b).…”
Section: Resultscontrasting
confidence: 84%
“…The curves were obtained by non‐linear curve‐fitting of the fluorescence intensity of the two probes and Cu 2+ with the correlation coefficients (R) over 0.95, which confirmed that 1 and 2 formed a 1:1 complex with Cu 2+ . The association constant K ass is calculated by using the following equation in the ORIGIN 7.0 software package: trueI=I0+4pt(Ilim-I0)/2c0{cH+cG+1/4ptKass4pt-[(cH+cG+1/4ptKass)2-4cnormalHcnormalG]4pt1/2} …”
Section: Resultsmentioning
confidence: 99%
“…The design and synthesis of anion-selective sensors have received considerable attention owing to the presence of multiple and various anionic species in both inorganic applications and biological systems [79][80][81][82]. Huang and coworkers [83], in their work, two anthryl-appended macrocycles 1 and 2 were synthesized, and their binding abilities toward transition metal ions were studied. Both of them show selectivity for Zn(II) over other metal ions (Cd(II), Co(II), Ni(II), and Cu(II)) by observed changes in their fluorescent spectra.…”
Section: Applicationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Historically, transition metal tetra-aza complexes have been utilized extensively in biomimetic inorganic chemistry as functional models for superoxide dismutase, catalase, and copper oxidase active sites. [18][19][20][21][22][23][24][25] Metal complexes derived from tetra-aza macrocyclic ligands generally present large stability constants, on the order of log K ≥ 20.0 in the case of copper(II) complexes.…”
Section: Introductionmentioning
confidence: 99%